2017
DOI: 10.1007/s13760-017-0764-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between migraine headache and asthma features

Abstract: Migraine and asthma are comorbid chronic disorders with episodic attacks thought to involve inflammatory and neurological mechanisms. The objective of the present study is to investigate the relationship of asthma features between the asthma patients with migraine and those without migraine headache. A cross-sectional study was conducted from October 2015 to June 2016. Physician-diagnosed asthma patients aged 18 years and above were included. Demographic data, pulmonary function test and treatment of asthma we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
2
7
0
1
Order By: Relevance
“…The exact pathway leading to comorbidity of migraine and asthma remains unclear. Previous studies have demonstrated an insight into the relationship between migraine and asthma from shared inflammatory, immune, and genetic factors (37)(38)(39). First, the bidirectional association between migraine and asthma is considered to be attributed to the common pathophysiological process of inflammation and immune dysfunction (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact pathway leading to comorbidity of migraine and asthma remains unclear. Previous studies have demonstrated an insight into the relationship between migraine and asthma from shared inflammatory, immune, and genetic factors (37)(38)(39). First, the bidirectional association between migraine and asthma is considered to be attributed to the common pathophysiological process of inflammation and immune dysfunction (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an insight into the relationship between migraine and asthma from shared inflammatory, immune, and genetic factors (37)(38)(39). First, the bidirectional association between migraine and asthma is considered to be attributed to the common pathophysiological process of inflammation and immune dysfunction (39). Studies have shown that allergic responses triggered by allergens, such as pollen, specific grass, release various inflammatory mediators or elevated neuropeptide mediated by mast cells, leading to hypersensitivity of airway responses in patients with asthma (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study investigating the risk of migraine in patients with asthma recently reported that the risk in the asthmatic group was 1.45-fold higher, compared to the non-asthmatic group (27). Similarly, two recent studies have also stated that patients with asthma have a high prevalence of migraine headaches (28,29). As reported in the mentioned studies, it is well established that there is a link between migraine and respiratory disorders, particularly asthma.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, we selected the fifth visit from the asthma index as the prediction date (testing set A) according to the average number of visits (5.78, SD 6.04) between asthma index and exacerbation among the patients. The detailed steps for the cohort selection are listed in Multimedia Appendix 1 [4,25,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In next-visit prediction, we simply set the penultimate visit as the prediction date (testing set B).…”
Section: Methodsmentioning
confidence: 99%